(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Witnessing the global arena many changes in the political, economic, social, scientific and technological have left their mark on the world as a whole, these changes require necessarily Advancement of the profession of auditing, and improve their performance, especially after the mixer skepticism the health of approach and the method followed by a check in the major audit firms global view as for the external audit of an active role in providing services to members of the community in various sectors, were to be provide these services to the highest level of quality.To ensure the quality of the audit process to be a proper planning is based on a scientific basis to be the substrate a strong underlying different audit works, and if planning important for the accomplish the audit process with high quality, the choice of technology that will be followed in planning no less important, and popped the problem not to resort to scientific methods in planning the audit process, implementation and limited to estimates personal auditors when determining audit procedures and when estimating the time required to perform the audit, and in the light of the study theory and practice that has been in the research has been to reach a set of conclusions and recommendations. Of the main conclusions, The style of PERT- CPM contributed to the reduction of the time the audit process through the coordination of activities in a scientific thoughtful, and achieved a surplus in the time it was possible to exploitation by the members of the audit team to carry out the other at the same work site or at other work sites, and then mitigate time pressures suffered by the members of the audit team and maintain the required level of professional care and the quality of work performed.The study provided a number of recommendations, including, Adoption of the proposed mechanism, which means planning the audit process and implemented according to the methods of time management, for providing clarify and simplify the application of the style of PERT- CPM in the audit process, and achieve these two methods of providing a scientific basis thoughtful planning, scheduling and follow-up and then raise the quality of the audit process.